The Arctic mineral resource rush and the ontological struggle for the Viiankiaapa peatland in Sodankylä, Finland - Lassila, Maija (Globalizations, 2022)
The Nordic states and the Arctic have recently received increasing attention as a consequence of the rush to excavate newly discovered mineral resources in the Global North. Local land struggles related to the expansion of the extractive industry need to be assessed and constitute the focus of the present article. I examine the deeper levels of conflict between the mineral resource rush and local people. I highlight local people's plural ways of being in relation to the land through an ethnographic exploration of a pivotal mining project in Arctic Finland being resisted by Finns, who live in a pro-mining municipality. These people experience a threat to the continuation of their lifeworlds when large-scale extraction enters their territories. However, achieving legitimacy for their lifeworlds has been difficult. The article suggests that a key reason for this lack of legitimacy is the dominant 'one' world ontology and its 'nature' knowledge practices. Peer reviewed